2015
DOI: 10.1080/ac.70.6.3120185
|View full text |Cite
|
Sign up to set email alerts
|

Erectile function in cardiovascular patients: its significance and a quick assessment using a visual-scale questionnaire

Abstract: ED is highly prevalent among cardiovascular patients. The Visual Scale Erectile Function questionnaire (VEF) is a simple and valid tool, suitable for quick screening of this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Recent studies have reported that alteration of the cyclic guanosine monophosphate (cGMP)/nitric oxide (NO) pathway among men with diabetes with impaired vascular relaxation is related to endothelial dysfunction (16)(17)(18). Among men with diabetes, risk factors include increasing age, duration of diabetes, poor glycemic control, cigarette smoking, hypertension, dyslipidemia, androgen-deficiency states (19) and cardiovascular disease (CVD) (6,11,12,(20)(21)(22)(23)(24).…”
Section: Erectile Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have reported that alteration of the cyclic guanosine monophosphate (cGMP)/nitric oxide (NO) pathway among men with diabetes with impaired vascular relaxation is related to endothelial dysfunction (16)(17)(18). Among men with diabetes, risk factors include increasing age, duration of diabetes, poor glycemic control, cigarette smoking, hypertension, dyslipidemia, androgen-deficiency states (19) and cardiovascular disease (CVD) (6,11,12,(20)(21)(22)(23)(24).…”
Section: Erectile Dysfunctionmentioning
confidence: 99%
“…In addition, studies indicate that 40% of men with diabetes greater than 60 years of age have complete ED (7-15).Recent studies have reported that alteration of the cyclic guanosine monophosphate (cGMP)/nitric oxide (NO) pathway among men with diabetes with impaired vascular relaxation is related to endothelial dysfunction (16-18). Among men with diabetes, risk factors include increasing age, duration of diabetes, poor glycemic control, cigarette smoking, hypertension, dyslipidemia, androgen-deficiency states (19) and cardiovascular disease (CVD) (6,11,12,(20)(21)(22)(23)(24).ED as a marker of potential cardiovascular (CV) events has been reported by numerous investigators (25-34). In fact, ED has been shown to be significantly associated with all-cause mortality and CV events (35)(36)(37).…”
mentioning
confidence: 99%
“…The bulk of AI discourse to date has surrounded the ability of AI systems to compress vast amounts of information to develop novel approaches to an accurate ED diagnosis that is seemingly more sensitive and specific than a clinician's medical decision‐making, thus minimizing errors in diagnosis. AI in diagnostics has been used to (Figure 2): Develop novel questionnaires that showed greater accuracy than the established International Index of Erectile Function (IIEF‐5) [ 34 ] ; Develop equipment such as corpus cavernosum electromyogram and digital inflection rigidometer analyzed to yield an ED diagnosis [ 35,36 ] ; Develop expert systems used as a clinical decision support system in men to diagnose ED without a physician following initial evaluation by questionnaires and equipment [ 7,37 ] ; Analyze medical images such as penile Doppler ultrasonography and positron emission tomography/computed tomography imaging of penile arteries in patients with prostate cancer to determine etiology of ED [ 38,39 ] ; Predict the onset or worsening of ED as a preoperative risk stratification for prostate cancer treatment, or predictive of postradiotherapy ED in men with prostate cancer [ 40–42 ] .…”
Section: Ai Applications In the Field Of Sexual Medicine And Men's He...mentioning
confidence: 99%
“…Develop novel questionnaires that showed greater accuracy than the established International Index of Erectile Function (IIEF‐5) [ 34 ] ;…”
Section: Ai Applications In the Field Of Sexual Medicine And Men's He...mentioning
confidence: 99%